Oral maintenance metronomic vinorelbine versus best supportive care in advanced non-small-cell lung cancer after platinum-based chemotherapy: The MA.NI.LA. multicenter, randomized, controlled, phase II trial. (June 2019) - Platania, Marco; Pasini, Felice; Porcu, Luca; Boeri, Mattia; Verderame, Francesco; Modena, Yasmina; Del Conte, Alessandro; Nichetti, Federico; Garassino, Marina Chiara; Martinetti, Antonia; Sottotetti, Elisa; Cavanna, Luigi; et al.
Highlights: This trial assessed switched-maintenance oral metronomic vinorelbine (OMV) in NSCLC. Patients who had not progressed after 1st-line Pt-based chemotherapy were enrolled. Patients were randomized to OMV or best supportive care (BSC). OMV prolonged PFS compared to BSC. The optimal dose of OMV requires further investigation. Abstract: Background: Oral vinorelbine administered at the maximum tolerated dose has already showed activity and a good safety profile in advanced non-small-cell lung cancer (NSCLC). The MA.NI.LA study was a phase II, multicenter, randomized, controlled trial that aimed to assess the effects of a 'switched maintenance' regimen with oral metronomic vinorelbine (OMV) in patients with NSCLC who had not progressed after first-line platinum-based chemotherapy. Patients and methods: Patients were randomly assigned in a 1:1 ratio to either OMV (50 mg three-times weekly) as maintenance treatment or best supportive care (BSC). The primary endpoint was progression-free survival (PFS). Secondary endpoints included overall survival (OS), objective disease control rate (DCR, CR + PR + SD), safety and quality of life. Results: In total, 61 and 59 patients were assigned to OMV and BSC, respectively. At a median follow-up of 23.9 (IQR 10.2–38.2) months, patients treated with OMV reported a significantly lower progression rate compared to patient in the BSC arm (89% [54/61] vs 96% [56/58]; HR 0.73; 90% CI 0.53-0.999, p = 0.049). Median PFS for patients treated with vinorelbine was 4.3 months (95% CI 2.8–5.6) vs 2.8 months (95% CI 1.9–4.5) for patients receiving BSC. This benefit was specifically evident in patients aged ≥70 years, in current smokers, and in those who reported disease stabilization as best response to induction chemotherapy. OS and response rate and quality of life were similar in the two arms. Drop-out rate for major toxicity with OMV was unexpectedly high (25%, 14/61) mainly due to grade 3–4 neutropenia (11%, 7/61). Conclusions In patients with unselected NSCLC achieving disease control after platinum-based chemotherapy switch maintenance therapy with OMV prolonged PFS compared to BSC; however, the optimal dose of OMV requires further investigation.